Nipple Sparing Mastectomy Minimally Invasive Video-Assisted Technique - Ferrari, Alberta; Sgarella, Adele; Zonta, Sandro; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2013)
This book describes in detail three different techniques for minimally invasive video-assisted breast surgery: nipple-sparing mastectomy with a hand-held external retractor, with a single-port device, and with robotic assistance. All three techniques can be employed for radical treatment of breast cancer or for risk reduction surgery, and the last two are brand new. The techniques are clearly explained with the aid of numerous high-quality illustrations. All surgical stages are covered in detail, and helpful information is provided on key aspects of surgical anatomy, diagnostic workup, instrumentation, and postoperative management. Nipple Sparing Mastectomy is the first manual to cover these techniques, which are likely to become standard in the field of oncological breast surgery. It will be invaluable for breast surgeons who are skilled in nipple-sparing mastectomy and oncoplastic techniques or are working in breast units that offer genetic counseling to high-risk patients.
1.History of the Mini Invasive Video Assisted Breast Surgery: From East to West -- 2.Surgical Anatomy of the Breast: Key Points for Mini Invasive Video Assisted Approach -- 3.Mini Invasive Video Assisted Breast Surgery: Feasibility and Safety -- 4.Indication for Mini Invasive Video Assisted Mastectomy -- 5.Diagnostic Work Out -- 6.Operative Instruments -- 7.Mini Invasive Video Assisted Mastectomy: Techniques -- 8.Reconstructive Options -- 9.Case Reports.
Keywords: Surgical oncology; Minimally invasive surgery; Surgical Oncology; Minimally Invasive Surgery